The moral implications of Kierkegaard's analysis of despair - Krishek, Sharon (Religious studies, 2016)
Kierkegaard's The Sickness unto Death famously characterizes despair as the sickness of any human being who does not live a life of faith. Kierkegaard supports this claim by providing a detailed analysis of despair in the first part of this essay. This analysis, I claim, presents the thesis that to be healed of despair is not only to maintain a correct relation to God but also to the world and, moreover, that the two relations are interdependent. Thus, in contrast to prominent readings of this essay, I claim that Kierkegaard's analysis of despair bears the important moral implication that a believer's relationship with other humans is indispensable to a life of faith.